Dielectric properties of addition and metathesis polynorbornenes with bulky side-substituents. (26th August 2020) - Karpov, Gleb O.; Alentiev, Dmitry A.; Wozniak, Alyona I.; Bermesheva, Evgeniya V.; Lounev, Ivan V.; Gusev, Yuri A.; Shantarovich, Victor P.; Bermeshev, Maxim V.
Abstract: Structure-property study of polynorbornenes for low dielectric permittivity materials was performed. Dielectric properties of various polynorbornenes bearing F-, Si- and alkenyl-side groups were investigated. The incorporation of both fluoroorganic- and Me3 Si-groups as side substituents was found to be a fruitful tool to tune dielectric properties and to obtain polymeric materials with low values of dielectric relative permittivity (hereinafter dielectric permittivity) and the dissipation factors. Addition polynorbornenes with Me3 Si- or alkenyl-side groups disclosed dielectric permittivity in the range of 2.07–2.34. Polynorbornenes containing fluouroorganic groups exhibited dielectric permittivity as low as 1.94–2.78. To the best of our knowledge, the achieved values of dielectric permittivity are the lowest ones among published for polynorbornenes. The investigated polymers also exhibited low or moderate values of the dissipation factor. The obtained results are considered and discussed along with the data of wide-angle X-ray diffraction, positron annihilating lifetime spectroscopy, low temperature nitrogen adsorption/desorption investigations. Graphical abstract: Image 1 Highlights: Structure-property study of polynorbornenes for low dielectric constant materials. Dielectric properties of two groups of polymers derived from Si-, F- and alkenyl-substituted norbornenes were studied. Incorporation of Me3 Si- and perfluoroalkyl-groups as side groups in polynorbornenes results in lowering dielectric constant. The lowest dielectric constants among polynorbornenes were achieved, and they were observed on PTCNSi2g and MPF16 films. Polynorbornenes studied possess a promising combination of properties: dielectric constant, water uptake, stability, etc.